Legal Protection of Ikat-Pahikung Woven Fabric Motifs in East Sumba Regency - Rambu Susanti Mila Maramba; Rambu Hada Indah; Pajaru Lombu (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Ikat weaving has been a source of employment, an important livelihood for the family and is widely recognized for a long time. One of the problems, in the last five years, has been the influx of